Evidence on the Heroin-Mediated Impairment of the Oxidative Status of Erythrocytes - Mohammad A. Bani-Ahmad; Ayman G. Mustafa; Abdelraheem A. Bani Ahmad; Islam E. Alkhazali; Ahmad A. Rahim (Journal of Toxicology)
Away from hemorheological properties, the effect of heroin addiction on erythrocytes is poorly investigated. This study aimed to investigate the oxidative impacts of heroin administration on erythrocytes. Study subjects included chronic intravenous heroin addicts and control subjects. Hematological analysis and redox parameters were measured, including serum concentration of methemoglobin ([MethHb]), serum glutathione peroxidase-1 ([GPX-1]), serum glutathione peroxidase (GPX) activity, erythrocytic protein carbonyl content, and oxidized to reduced glutathione (GSSG/GSH) ratio. Hematological analysis revealed that addicts had a significantly higher red cell distribution width, consistent with the mild anisocytosis and poikilocytosis of erythrocytes. As compared to control subjects, significantly higher levels of serum [Met-Hb], [GPX-1], and GPX activity (p<0.001) were reported among addicted subjects. A significant association between [MetHb] and GPX activity was observed with r = 0.764 (p<0.001). Furthermore, significantly higher erythrocytic protein carbonyl contents and GSSG/GSH ratio were evident among heroin addicts (p<0.005) that were significantly associated with r = 0.429 (p=0.01). Results demonstrate preliminary evidence that heroin addiction is implicated in impaired redox status of erythrocytes. Considering the pharmacokinetics of heroin, erythrocytic antioxidant mechanisms, and turnover rate, further investigation is required to evaluate the extent and clinical outcomes, especially upon over-dose administration.